ApoE4 May be a Promising Target for Treatment of Coronary Heart Disease and Alzheimer's Disease - Chen, Wei; Jin, Fengzhong; Cao, Guihua; Mei, Rong; Wang, Yayun; Long, Pan; Wang, Xiaoming; Ge, Wei (Current Drug Targets, 2018)
Alzheimer disease (AD) is most common neurodegenerative disorder of dementia, as we all know that ApoE4 is the greatest genetic risk factor of late-onset Alzheimer's disease (LOAD). Coronary heart disease (CHD) leads to one-fourth of all deaths in industrialized countries, it is reported that ApoE4 increases the risk of coronary heart disease as well. Furthermore, evidence show that coronary heart disease also increases the incidence of Alzheimer's disease. Whether ApoE4 is a bridge connecting AD with CHD or not? And what are the special mechanism and therapeutic methods? Researchers found that cholesterol metabolic disorder is the common cause and risk factor of AD and CHD. Epidemiological studies demonstrate that carriers of the ApoE4 allele have higher cholesterol plasma concentration. More evidence indicate that hypercholesterolemia accelerates the progression of coronary atherosclerosis, damages the central nervous system blood-brain barrier, promotes Aβ protein production and Tau deposition in brain. Therefore, ApoE4 is likely to be the bridge between AD and CHD, and may be a potentially promising therapeutic target.
Keywords: ApoE4